2021
DOI: 10.7150/jca.48387
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-32-5p inhibits epithelial-mesenchymal transition and metastasis in lung adenocarcinoma by targeting SMAD family 3

Abstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer-associated death worldwide. MicroRNA (miRNA)-32-5p is as an important cancer-associated miRNA in different types cancer. To date, the role of miR-32-5p in the migration and invasion of NSCLC remains unknown. In the present study, a Transwell assay was performed to investigate the role of miR-32-5p in lung adenocarcinoma. miR-32-5p expression level was determined via reverse transcription-quantitative PCR in 24 pairs of NSCLC and adjacent normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Through mRNA-miRNA-lncRNA network construction, the lncRNA KCNQ1OT1 / hsa-miRNA-32-5p / PER2 / CRY2 regulatory axis was identified. Previous studies have reported that miRNA-32-5p regulates the progression of gastric cancer and epithelial-mesenchymal transition and metastasis in lung adenocarcinoma [ 43 , 44 ]. However, studies concerning the role of miRNA-32-5p in COAD are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Through mRNA-miRNA-lncRNA network construction, the lncRNA KCNQ1OT1 / hsa-miRNA-32-5p / PER2 / CRY2 regulatory axis was identified. Previous studies have reported that miRNA-32-5p regulates the progression of gastric cancer and epithelial-mesenchymal transition and metastasis in lung adenocarcinoma [ 43 , 44 ]. However, studies concerning the role of miRNA-32-5p in COAD are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, miRNAs may also inhibit metastasis. MiRNA-32-5p inhibits EMT and metastasis in lung adenocarcinoma by targeting SMAD3 ( Zhang J.-X. et al, 2021 ), miR-16-1-3p suppresses breast cancer growth and metastasis by inhibiting Warburg Effect ( Ye et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that knockdown of NEAT1 promotes apoptosis by sponging miR-153-3p, thereby inhibiting cell proliferation, migration, and invasion in NSCLC [40]. miRNA-32-5p has been reported to inhibit epithelial-mesenchymal transition (EMT) and metastasis in LUAD by targeting SMAD family 3 (SMAD3) [41]. In addition, the expression of miR-890 was negatively regulated by small nucleolar host gene 3 (SNHG3).…”
Section: Discussionmentioning
confidence: 99%